2012
DOI: 10.4311/2011es0222
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization based on water chemistry and physicochemical traits in the ring of cenotes, Yucatan, Mexico

Abstract: Assessing water quality in aquifers has become increasingly important as water demand and pollution concerns rise. In the Yucatan Peninsula, sinkholes, locally known as cenotes, are karst formations that intercept the water table. Cenotes are distributed across the peninsula, but are particularly dense and aligned along a semicircular formation called the Ring of Cenotes. This area exhibits particular hydrogeological properties because it concentrates, channels, and discharges fresh water toward the coasts. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
3
25
0
1
Order By: Relevance
“…), covering 11 municipalities of Yucatan, Mexico, and was taken from a study by Pérez‐Ceballos et al . (Table ). The climate is warm and humid, with an average temperature of 25–27°C.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…), covering 11 municipalities of Yucatan, Mexico, and was taken from a study by Pérez‐Ceballos et al . (Table ). The climate is warm and humid, with an average temperature of 25–27°C.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Location of the study area in the State of Yucatan along with average annual precipitation isohyets. The dots represent the locations of some sinkholes within the ring of sinkholes delimited by the two semicircles (Pérez‐Ceballos et al ). Contours of precipitation are adapted from PROCOMAR ().…”
Section: Introductionmentioning
confidence: 99%
“…The aquifer is highly vulnerable to contamination, as shown by previous studies that reported that groundwater within the top 15 to 20 m of the aquifer does not meet the standards for human consumption (Marín et al ; Pacheco‐Castro et al ). Six kilometers to the east of our study site, Pérez‐Ceballos characterized a group of seven cenotes with low pH values, high NO3, and high Ca2+ and HCO3 and concluded that these cenotes in the center of the RC are in an aquifer recharge zone (Pérez‐Ceballos et al ).…”
Section: Site Descriptionmentioning
confidence: 94%
“…The ERTs were performed to obtain information on possible underground water cavities which connect cenotes. The water in the region studied has a resistivity between 6 and 12 ohm‐m (Pérez‐Ceballos et al ) but since the inversion process introduces a degree of uncertainty, we consider a larger range for the resistivity: 1 to 47 ohm‐m. Later in the paper, we will see evidence for 23 water cavities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation